Adsorption behavior of magnetic bentonite for removing Hg(ii) from aqueous solutions. Issue 48 (2nd August 2018) - Zou, Chenglong; Liang, Jiyan; Jiang, Wei; Guan, Yinyan; Zhang, Yichen
Abstract : Bentonite is a porous clay material that shows good performance for adsorbing heavy metals in wastewater remediation. Magnetic bentonite (M-B) was prepared and it was successfully used as an adsorbent to remove Hg(ii ) from aqueous solutions in this paper. Abstract : Bentonite is a porous clay material that shows good performance for adsorbing heavy metals and other pollutants for wastewater remediation. However, it is very difficult to separate the bentonite from water after adsorption as it forms a stable suspension. In this paper, we prepared magnetic bentonite (M-B) by loading Fe3 O4 particles onto aluminum-pillared bentonite (Al-B) in order to facilitate its removal from water. The functional groups, skeleton structure, surface morphology and electrical changes of the prepared material were investigated by FT-IR, XRD, BET, SEM, VSM and zeta potential measurements. It was used as an adsorbent for Hg(ii ) removal from aqueous solutions and the influence of various parameters on the adsorption performance was investigated. The adsorption kinetics were best fitted by the pseudo-second-order model, and also followed the intra-particle diffusion model up to 18 min. Moreover, adsorption data were successfully reproduced by the Langmuir isotherm, and the Hg(ii ) adsorption saturation capacity was determined as 26.18 mg g −1 . The average adsorption free energy change calculated by the D-R adsorption isotherm model was 11.89 kJ mol −1, which indicated the occurrence of ionic exchange. The adsorption thermodynamic parameter Δ H was calculated as 42.92 kJ mol −1, which indicated chemical adsorption. Overall, the thermodynamic parameters implied that Hg(ii ) adsorption was endothermic and spontaneous.